Rare concurrence of ectopic intrathyroidal parathyroid gland and papillary thyroid carcinoma within a thyroid lobe: A care-compliant case report. Issue 34 (August 2019) - Chen, Jianguo; Wan, Yingying; Chen, Shuguang
Abstract: Rationale: The inferior parathyroid glands derive from the third branchial pouch and seldom ectopically migrate to thyroid grand, mediastinum, thymus. Ectopic intrathyroidal parathyroid grand (ETPG) is rare and it cannot be consistently detected by any imaging examinations. The unusual ETPG is easily resected during thyroidectomy, which might cause postoperative hypoparathyroidism. Auto-transplantation of even a parathyroid gland can restore parathyroid function to some extent. Until now, there are not any guidelines on the management of ETPG. Patient concerns: Without any symptoms, a 27-year-old female patient was admitted to our hospital for a thyroid nodule. Thyroid ultrasonography demonstrated a hypoechoic nodule, measuring 0.6 cm × 0.6 cm × 0.7 cm, with multiple punctate micro-calcifications within the right thyroid lobe. Thyroid function tests were normal. The invasive fine needle aspiration cytology for the thyroid nodule was rejected by patient. Diagnoses: The patient was firstly diagnosed as right thyroid hypoechoic nodule, which was pathologically proved to be papillary thyroid carcinoma (PTC) finally. Interventions: The patient underwent right thyroidectomy, central compartment neck dissection, parathyroid exploration, and auto-transplantation of the normal ETPG. Outcomes: The right thyroid hypoechoic nodule was diagnosed as PTC by pathological examination. The inferior parathyroid gland could not found in normal locations. On the cut surface of excised thyroid lobe, a yellow and soft nodule was discovered and it was pathologically diagnosed as a normal parathyroid grand. In the end, auto-transplantation of the normal ETPG was conducted. Postoperative follow-ups found both serum calcium and parathyroid hormone tests were normal. Lessons: ETPG in a patient with PTC is easily overlooked and unexpectedly excised for its rarity. ETPG brings about a failed parathyroid exploration. However, within the thyroid parenchyma, it might be occasionally discovered by cutting a thyroid lobe into slices. Auto-transplantation of normal ETPG is necessary.